Elevated D‐dimers in attacks of hereditary angioedema are not associated with increased thrombotic risk. Issue 5 (23rd February 2015) - Reshef, A.; Zanichelli, A.; Longhurst, H.; Relan, A.; Hack, C. E.
Abstract Background Recommended management of attacks of hereditary angioedema (HAE) due to C1 esterase inhibitor (C1‐INH) deficiency (C1‐INH‐HAE) includes therapy with exogenous C1INH. Thrombotic/thromboembolic events (TEE) have been reported with plasma‐derived C1INH, but so far none with recombinant human C1INH (rhC1INH). This phase III, randomized, placebo (saline)‐controlled study evaluated the safety of rhC1INH 50 IU/kg for the treatment of acute attacks in 74 patients with C1‐INH‐HAE. Methods Monitoring for TEE and assessment of risk of deep vein thrombosis (DVT) by the Wells prediction rule were performed, and levels of fibrin degradation products (plasma D‐dimers) were assessed before study drug administration (baseline), 2 h, and 7 days posttreatment. Results Plasma D‐dimer levels were elevated in 80% of the patients (median [25th–75th percentiles]: 2149 [480–5105] μg/l; normal ≤250 μg/l) and were higher in patients with submucosal (abdominal, oropharyngeal–laryngeal) attacks (3095 [890–10000] μg/l; n = 29) compared with subcutaneous (peripheral, facial) attacks (960 [450–4060] μg/l; n = 35). Median plasma D‐dimer levels were comparable across treatment groups at baseline (1874 [475–4568] μg/l rhC1INH; 2259 [586–7533] μg/l saline) and 2 h postinfusion (2389 [760–4974] μg/l rhC1INH; 2550 [310–8410] μg/l saline); median plasma D‐dimer levels were decreased by Day 7 in both groups (425 [232–3240] μg/l rhC1INH; 418 [246–2318] μg/l saline). No increased risk of DVT was identified, nor any TEE reported in rhC1INH treated or controls. Conclusion Elevated plasma D‐dimer levels were associated with acute C1‐INH‐HAE attacks, particularly with submucosal involvement. However, rhC1INH therapy was not associated with thrombotic events.